MEMPELAJARI REAKSI ISOMERISASI SAFROL DENGAN PEREAKSI KOH/n-BuOH DAN NaOH/CH2OHCH2OH - Fatimah, Feti (Sainstek, 2009)
The studies have been done about the transformation of safrole into isosafrole. The transformation was done using reagents, namely KOH/n-BuOH and NaOH/CH2OHCH2OH. The purities of all products were tested with thin layer and gas chromatography. Thereafter the structures were identified with infrared spectrophotometers, NMR1H and 13C spectrometry, and mass spectrometry. The isomerization product of safrole into isosafrole with highest percentage yield (75%) was given NaOH/CH2OHCH2OH.